2008
DOI: 10.1080/09513590802128968
|View full text |Cite
|
Sign up to set email alerts
|

Plasma cytokines in obese women with polycystic ovary syndrome, before and after metformin treatment

Abstract: In the PCOS group significantly lower plasma adiponectin and TNFalpha levels were observed, whereas there were no differences in plasma IL-6 and CRP levels between PCOS and control groups. Plasma adiponectin increased significantly after metformin treatment, but levels of inflammatory factors did not change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 39 publications
4
52
1
1
Order By: Relevance
“…The association of IR and hyperinsulinemia of PCOS with elevation of various cytokines such as IL-4, IL-6, TNF-a, and their alteration after treatment with insulin sensitizers is well established (9,10). Elevated fasting insulin and HOMA-IR, indicative of significantly higher IR in both of our PCOS and non-PCOS sub-groups of CLT girls when compared to controls, may indicate some pathogenic link between autoimmunity and IR (12,13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association of IR and hyperinsulinemia of PCOS with elevation of various cytokines such as IL-4, IL-6, TNF-a, and their alteration after treatment with insulin sensitizers is well established (9,10). Elevated fasting insulin and HOMA-IR, indicative of significantly higher IR in both of our PCOS and non-PCOS sub-groups of CLT girls when compared to controls, may indicate some pathogenic link between autoimmunity and IR (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Women with PCOS have been demonstrated to have elevated cytokines like tumour necrosis factor-a (TNF-a) and IL-6 concentrations independent of obesity, and these alterations in serum inflammatory markers in PCOS are unrelated to PPAR-g variants (9). It has been demonstrated that the therapy with metformin in PCOS leads to an increase in plasma adiponectin and TNF-a but not plasma IL-6 and C reactive protein (CRP) (10). Some authors demonstrated a high prevalence of autoimmune thyroiditis in PCOS women suggesting a potential pathogenic link with autoimmunity/sub-inflammatory cascade (11).…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34][35][36][37] We attribute these differences to several factors, such as the diagnostic criterion for the syndrome, the presence of CV risk factors and the presence of obesity itself. In this study we sought to select such a group of women that would avoid such bias and, through the employment of a select statistical method, to separate the confounding effect of PCOS and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, obesity, predominantly abdominal, is recognized as an important determinant of metabolic risk in these patients (Azziz et al, 2004;Spritzer and Wiltgen, 2007). In PCOS, elevated leptin serum levels have been associated with amount of adipose tissue, waist circumference, insulin resistance, and hyperandrogenemia (Spritzer et al, 2001;Carmina et al, 1999Carmina et al, , 2005, while adiponectin levels have been reported to be decreased (Ardawi and Rouzi, 2005;EscobarMorreale, 2006;Jakubowska et al, 2008;Carmina et al, 2005Carmina et al, , 2009 or unchanged (Orio et al, 2003;Sprangler et al, 2004;Gulcelik et al, 2006). In this paper, we briefly review the emerging evidence linking adipose tissue expression of leptin and adiponectin and serum adipokine levels in women with PCOS.…”
Section: Introductionmentioning
confidence: 99%